2012
DOI: 10.1021/nl302398m
|View full text |Cite
|
Sign up to set email alerts
|

Interface Formation in Monolayer Graphene-Boron Nitride Heterostructures

Abstract: The ability to control the formation of interfaces between different materials has become one of the foundations of modern materials science. With the advent of two-dimensional (2D) crystals, low-dimensional equivalents of conventional interfaces can be envisioned: line boundaries separating different materials integrated in a single 2D sheet. Graphene and hexagonal boron nitride offer an attractive system from which to build such 2D heterostructures. They are isostructural, nearly lattice-matched, and isoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
273
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(287 citation statements)
references
References 39 publications
11
273
2
1
Order By: Relevance
“…Recently, patterned regrowth 12,13 has been attempted for the spatially controlled synthesis of lateral junctions between electrically conductive graphene and insulating h-BN to make integrated circuitry 12 . The successful interfacing of these two isoelectronic materials to form hybrid monolayer film on Ru was also demonstrated by Sutter et al It is reported that the elimination of residual carbon adatoms is crucial to prevent unintentional intermixing of the G-BN interfaces 11 . In contrast to spatially segregated G-BN composite, intermixing of B, C and N atoms under thermodynamic non-equilibrium conditions may lead to semiconducting h-BC x N alloys 9,14,15 .…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Recently, patterned regrowth 12,13 has been attempted for the spatially controlled synthesis of lateral junctions between electrically conductive graphene and insulating h-BN to make integrated circuitry 12 . The successful interfacing of these two isoelectronic materials to form hybrid monolayer film on Ru was also demonstrated by Sutter et al It is reported that the elimination of residual carbon adatoms is crucial to prevent unintentional intermixing of the G-BN interfaces 11 . In contrast to spatially segregated G-BN composite, intermixing of B, C and N atoms under thermodynamic non-equilibrium conditions may lead to semiconducting h-BC x N alloys 9,14,15 .…”
mentioning
confidence: 77%
“…S2). In the work reported by Sutter et al 11 , shallow lines were imaged in the mixed BCN (boron-carbonnitride) regions. These lines appeared to be relatively disordered and their atomic structures and chemical composition were unknown.…”
Section: Mixing and Demixing Of Bn And C Phases On Ru(0001)mentioning
confidence: 98%
See 1 more Smart Citation
“…Progress in this direction has been limited by difficulties in achieving scalable growth of uniform h-BN layers using chemical vapour deposition, a technique used to deposit high-quality graphene layers [11][12][13][14][15][16][17][18][19] . There have also been a few attempts to co-deposit graphene and h-BN domains to build hybridized two-dimensional boron carbonitride (h-BNC) atomic layers [10][11][12][13][14][15][16][17][18][19][20][21][22] . This coexistence of seamless graphene and h-BN domains inspires us to explore the synthesis of large area and high-quality h-BN atomic layers by substitutions of carbon atoms in graphene with boron and nitrogen.…”
mentioning
confidence: 99%
“…Sequential growth of graphene/ h ‐BN on catalytic metal surfaces via chemical vapor deposition (CVD) has been extensively studied to form in‐plane heterostructure 9, 10, 14, 15, 16, 17, 18, 19, 20. Templated growth of h ‐BN starting from CVD graphene edges on copper has been realized with lattice coherency of the two crystals 14, 16.…”
mentioning
confidence: 99%